Pragmatism, Education, and Children : International Philosophical Perspectives. - Taylor, Michael, 1944- (Value Inquiry Book Series, 2008)
This book presents fourteen new essays by international scholars about the intersections between pragmatism, education, and philosophy with children. Pragmatism from its beginnings has sought a revolution in learning, and is itself a special kind of philosophy of education. What can the applications of pragmatism to pedagogy around the world teach us today?